Effectiveness of Dried Juwet Cereal Bar (Syzygium cumini L.) as an Antianemic Intervention in Lead-Induced Female White Rats: A Preclinical Study - Ni Luh Putu Anggie Pramesthi Putri; Ni Komang Puja Pertiwi; Anak Agung Cahaya Dayita Nariswari; Shiendy Ayu Puspita; Ni Putu Ayu Widya Anggreni; Ketut Agus Adrianta (Poltekkes Kemenkes Surabaya, 2025)
In contemporary times, lifestyle changes and increased air pollution from vehicle emissions have impacted health, particularly through chronic lead exposure. Lead disrupts iron absorption and hemoglobin synthesis, leading to anemia—a condition marked by insufficient red blood cells or hemoglobin. Anemia affects 29.9% of women of reproductive age globally, with notably high rates in Indonesia among pregnant women and adolescent girls. Tradition al iron supplements often cause side effects, highlighting the need for alternative non-pharmacological solutions. Syzygium cumini L., which is rich in iron, vitamin C, and anthocyanins, offers a promising alternative. This study evaluates the effectiveness of Dried Juwet Cereal Bar in treating anemia using a quantitative experimental approach. Twenty-eight female rats were divided into four groups: negative control, positive control, normal, and treatment, receiving Dried Juwet Cereal Bar containing 5.9% juwet extract. Hemoglobin, hematocrit, and erythrocyte levels were measured using a hematologic analyzer, with statistical analyses performed using paired sample T-tests, Kruskal-Wallis tests, and Mann-Whitney tests. The juwet extract, prepared with a 96% ethanol-water mixture, retained significant bioactive compounds. Phytochemical screening revealed alkaloids, flavonoids, triterpenoids, saponins, and anthocyanins. The extract showed high antioxidant activity (IC50 of 215.6887 ppm) and a substantial vitamin C content (18,586.7 mg/100 g). Results indicated that Dried Juwet Cereal Bar significantly increased hemoglobin, hematocrit, and erythrocyte levels after administering dried juwet cereal bars in anemic female white rats with a p-value<0,05, suggesting their potential as an effective non-pharmacological treatment for anemia. This approach supports local agriculture and provides a nutritious, practical, and sustainable product reflecting Indonesian tropical fruit diversity.